Visceral pleural invasion by pulmonary adenocarcinoma ≤3 cm: the pathological correlation with pleural signs on computed tomography - Yang, Shuyi; Yang, Liang; Teng, Lin; Zhang, Shan; Cui, Yue; Cao, Yukun; Shi, Heshui (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: (I) To categorize and quantitatively analyze pleural signs on CT of pulmonary adenocarcinoma (≤3 cm); (II) to evaluate the association between pleural signs and visceral pleural invasion (VPI) of adenocarcinoma. Methods: The clinical data of 52 pulmonary adenocarcinoma patients with 91 involved pleurae were retrospectively analyzed in one single institution. Pleural signs were categorized into five types of non-interlobar fissure pleura (group A) and four types of interlobar fissure pleura (group B). A new parameter called pleural indentation fraction (PIF) was firstly defined to quantitatively evaluate the level of pleural shift. Results: In group A, type I pleural sign accounted for 15.79%, type II for 31.58%, type III for 21.05%, type IV for 10.53%, type V for 21.05%. The PIF of type II–III was 0.494±0.204. In group B, type I accounted for 67.65%, type II for 14.71%, type III for 8.82%, type IV for 8.82%. The PIF of type I was 0.188±0.083, significantly different with type II–III of group A (t=−7.444, P